Measuring the Impact of Nuclear Interaction in Particle Therapy and in Radio Protection in Space: the FOOT Experiment - Battistoni, Giuseppe; Toppi, Marco; Patera, Vincenzo; The FOOT Collaboration, (Frontiers in Physics, 2021)
Charged Particle Therapy (PT) uses proton or 12C beams to treat deep-seated solid tumors, and due to the advantageous characteristics of charged particles energy deposition in matter, the maximum of the dose is released to the tumor at the end of the beam range, in the Bragg peak region. However, the nuclear interactions of the beam nuclei with the patient tissues induce fragmentation both of projectile and target nuclei and need to be carefully taken into account when planning the treatment. In proton treatments, the target fragmentation can induce low energy, short range fragments along all the beam path, that may deposit a non-negligible dose in the entry channel. On the other hand in treatments with 12C, or other possible ions of interest, like 4He or 16O, the main concern is long range fragments, produced by projectile fragmentation, that release their dose in the healthy tissues beyond the Bragg peak. The same nuclear process is of increasing interest for radiation protection in human space flight, in view of deep space missions. In particular 4He and high-energy (E) and charge (Z) particles (HZE), mainly 12C, 16O, 28Si and 56Fe, provide the main contribution to the equivalent dose in deep space. The nuclear fragmentation properties of the materials used in the spacecrafts need to be known with high accuracy in order to provide the required shielding of the astronauts against such space radiation. The study of the impact of these processes, of interest to both PT and space radioprotection, at present suffers from the still significant lack of experimental data concerning the relevant nuclear cross sections, while the available computational models are not yet sufficiently reliable. The FOOT (FragmentatiOn Of Target) collaboration, composed of researchers from France, Germany, Italy and Japan, designed an experiment to study these nuclear processes and measure the corresponding fragmentation cross sections. In this work we discuss the physics motivations of FOOT, describing in detail the present detector design and the expected performances, coming from the optimization studies and beam test results. The plan of measurements to be performed will be also presented.